Lily, la ruidosa - Laguna, Sofie, 1968-; Argent, Kerry, 1960- (New York : Scholastic Press, 2004)
Lily's family and friends often complain that she is too loud, but that loudness makes her a hit in the school play.
Keywords: Noise -- Fiction; Hippopotamus -- Fiction; Animals -- Fiction; Spanish language materials